Reliability evaluation of distribution system integrated with distributed generation - Ch. V. S. S. Sailaja; Polaki V. N. Prasad (Bulletin of Electrical Engineering and Informatics, 2022)
Distributed generation (DG) improves the reliability of the system by providing a means of alternate power supply to the load points. DG is integrated to meet the system load along with the utility. In this work roy billinton test system (RBTS) bus 4 is considered for evaluating the effect of DG integration on system reliability. Reliability is evaluated using failure modes and effect analysis (FMEA) technique and the results are validated using Monte Carlo simulation technique. A MATLAB program is developed for both the techniques to evaluate the reliability. The failure rate of DG and the islanding capability of the DG are considered to resemble the practical operating conditions of DG. When DG is operating in islanded mode, if DG fails it affects the outage time of the load points. DG failure rate is also considered as the second order failure event overlapping with the feeder section failures. All the practical operating conditions of DG considered and their effect on the reliability of the system is evaluated.